EFFECT OF JOINT ROUGHNESS ON DIRECT SHEAR TEST. - Kartini
Rock mass has discontinuities such as joint, bedding plane, fault, etc. These discontinuities may reduce rock shear strength. Shear strength affect stability of excavation. One of factor which affect the shear strength of rock is surface roughness of discontinuities or joint roughness. In this research have done evaluated on direct shear test result of discontinuity with nine types of asperity angle (i) are 10, 15, 20, 25, 30, 35, 40, and 45 degrees. Sample material has made from gypsum flour and water with rasio 1 : 0,75 by weight. The sample have trapesium block shape with surface area 96 x 136,5 mm. The direct shear test has done by CNL method (constant normal load) with four normal force as 0,2; 0,4; 0,6; and 0,8 kN. The rate of shear displacement has set at 0,5 mm/menit. The result of the research show that shear strength increase as increasing of asperity angle. But will decrease after 30 degrees because of the surface of roughness shearing. For asperity angle less than 30 degrees just have sliding behaviour during test. The result have compared with emphirical criterion such as Patton (1966), Ladanyi dan Archambault (1970), dan Barton (1973, 1976). Based on Budi, et al. (2014) for Barton equation need for modification because it doesn’t considered shear area ratio and degree of interlocking. The result also simulate with numerical method using phase2 program for angle of asperity 5 degrees.